Neottia wuyishanensis (Orchidaceae: Neottieae), a new species from Fujian, China - Bing-Hua Chen (KeAi Communications Co., Ltd., 2021)
A new species, Neottia wuyishanensis (Neottieae, Orchidaceae), is described and illustrated from Wuyishan, Fujian, eastern China, based on morphological characters and molecular data. Molecular phylogenetics indicate that N. wuyishanensis is nested within the clade formed by Neottia fugongensis and Neottia nujiangensis. Morphologically, N. wuyishanensis is similar to N. fugongensis and N. pseudonipponica, but differs from them by having indistinct auricles at the base, and in the shape and size of lobelets.